Design and Development of a Novel Thermochemical Reactor Using Composite Sorbent for Solar Thermal Energy Storage - Nejhad, Majid Karim (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Thermochemical heat storage (THS) is being considered as a potential technology in order to enhance the utilization of renewable energy sources due to its high energy storage density and long term heat storage capacity. However, further advancement in such systems depends on the development of novel sorption materials and innovative solar-driven thermochemical processes. To this end, this work presents new sorption materials and a new solar-driven THS process suitable for building applications. In the first part of the study, two novel composite sorbents consisting of aerated porous concrete-calcium chloride (APC-CaCl2) and pumice-calcium chloride (P-CaCl2), respectively, were synthesized. Other than the synthesized new composite materials, vermiculite-calcium chloride (V-CaCl2) and zeolite were also selected and synthesized for a comparative performance study. A new experimental scale THS system was designed and developed for investigating the charging/discharging characteristics of all synthesized sorption materials. The experimental results show that, the values of the average energy storage density of the system operating with APC-CaCl2, V-CaCl2, zeolite, and P-CaCl2, for five hours of discharging were 186.9 kWh/m3, 174.2 kWh/m3, 182.6 kWh/m3 and 204.3 kWh/m3, respectively. For a charging temperature of 90 ºC over three hours of charging process, the mass desorption rate of APC-CaCl2 was found to be 9.84 g/min, while, it was 4.40 g/min, 13.27 g/min and 14.13 g/min for zeolite, V-CaCl2 and P-CaCl2, respectively. Considering their charging/discharging performances and their cyclic stability, P-CaCl2 and V-CaCl2 were found to be the best candidate materials for THS applications. In the second part of the study, a solar-driven THS was designed, developed and tested under real climatic conditions of North Cyprus. V-CaCl2 was selected as the working material due to its high energy density, good cyclic ability and the low cost and availability of vermiculite (host matrix) in North Cyprus. Three series of charging-discharging experiments were performed employing the newly developed solar-driven THS system. The discharging tests were performed during the night for a duration of five hours. During the discharging experiments, the temperature and relative humidity of air at the reactor inlet were in the range of 21 – 24 ºC and 80 – 90 %, respectively. Under these conditions, the average energy output over three cycles was found to be 2.1 kWh, with an average energy storage density of 156 kWh/m3. A manufactured parabolic solar concentrator was utilized to provide the required thermal energy in the charging process. Hence, the average surface temperature of the reactor was in the range of 78 ºC to 83 ºC and the average useful energy of the charging process was 3.94 kWh. The rate of moisture desorption was 6.5 g/min while the overall efficiency was 38%. Furthermore, an economic analysis was performed to compare the feasibility of the proposed solar-driven THS system and a typical heat-pump unit of the split air-conditioner under the climatic conditions of North Cyprus. The heating load of a house with an area of 90 m2 was simulated in the DesignBuilder software, and from the simulation results, it was found that a solar-driven THS system with a reactor volume of 8.75 m3 is required to meet 1366 kWh of an annual heating load of the building. The analysis showed that the net present value of THS system after ten years would be $381 with a simple payback period of 6.4 years, which illustrates the economic feasibility of the THS system. Keywords: Thermochemical Heat Storage, Solar Energy, Thermodynamic Analysis, Porous Host Matrix, Calcium Chloride, Composite Sorbent, Experimental

ÖZ: Termokimyasal ısı depolama (TID) sistemleri, ısıl enejiyi yüksek yoğunlukta ve uzun süreli olarak depolayabilme imkanı sağladığından, yenilenebilir enerji kaynaklarından daha verimli faydalanmak için potansiyel bir teknoloji olarak görülmektedir. Ancak TID sistemlerinin gelişimi, yenilikçi ısı depolama malzemelerinin ve etkin güneş enerjili TID proseslerinin geliştirilmesine bağlıdır. Bu bağlamda sunulan çalışmada bina uygulamalarına yönelik geliştirilen yeni sorpsiyon malzemelerinin ve güneş enerjisi kaynaklı TID sisteminin performansları deneysel olarak incelenmiştir. Çalışmanın ilk kısmında gözenekli beton-kalsiyum klorür (APC-CaCl2) ve pomza-kalsiyum klorür (P-CaCl2) olmak üzere iki yeni kompozit sorbent sentezlenmiştir. Bunun yanında performans karşılaştırması amacıyla Zeolit ve vermikülit-kalsiyum klorür (V-CaCl2) seçilmiş ve sentezlenmiştir. Daha sonra laboratuvar ölçekli bir deneysel TID sistemi tasarlanıp üretilmiş ve hazırlanan tüm sorbentler, şarj/deşarj performans karakteristiklerinin belirlenmesi amacıyla test edilmiştir. Deneysel çalışma sonuçlarına göre, beş saat deşarj süresi için APC-CaCl2, V-CaCl2, Zeolit ve P-CaCl2’nin enerji depolama yoğunlukları sırasıyla 186.9 kWs/m3, 174.2 kWs/m3, 182.6 kWs/m3 ve 204.3 kWs/m3 olarak hesaplanmıstır. Bunun yanında 90 ºC şarj sıcaklığı ve üç saatlik şarj süresinde, su buharı desorpsiyon hızları APC-CaCl2, Zeolit, V-CaCl2 ve P-CaCl2 için 9.84 g/dak 4.40g/dak, 13.27g/dak ve 14.13g/dak olarak belirlenmiştir. Şarj/deşarj performansları ve çevrimsel kararlılık parametreleri göz önüne alındığında P-CaCl2 ve V-CaCl2 TID uygulamaları için en uygun sorbentler olarak belirlenmiştir. Çalışmanın ikinci kısmında, güneş enerjisi kaynaklı bir TID sistemi tasarlanmış, geliştirilmiş ve Kuzey Kıbrıs iklim koşullarında test edilmiştir. Yüksek enerji depolama yoğunluğu, etkin çevrimsel kararlılığı, düşük maaliyeti ve Kuzey Kıbrıs’ta bulunabilirliği göz önüne alınarak, geliştirilen deneysel sistemde sorbent malzemesi olarak V-CaCl2 kullanılmıştır. Deneysel süreçte, geliştirilen güneş enerjili TID sistem performansını ölçmek için üç tekrar eden şarj/deşarj çevrimi yapılmıştır. Deşarj testleri güneş ışınımın olmadığı akşam saatlerinde beş saatlik sürede gerçekleştirilmiştir. Deşarj testleri sırasında reaktör giriş havası sıcaklığı ve bağıl nemi sırasıyla 21 – 24 ºC ve 80% – 90% arasında ölçülmüştür. Belirtilen çalışma koşulları altında deşarj prosesi averaj ısı üretimi ve enerji depolama yoğunluğu üç tekrar eden çevrim için sırasıyla 2.1 kWs ve 156 kWs/m3 olarak hesaplanmıştır. Sorpsiyon reaktörüne entegre edilen parabolik güneş yoğunlaştırıcısı şarj prosesinde gerekli ısıl enerjiyi üretmek için kullanılmıştır. Şarj sırasında reaktör ortalama sıcaklığı 78 ºC – 83 ºC arasında ölçülmüş, güneş ışınımından elde edilen kullanılabilir ortalama ısıl enerji değeri 3.94 kWs olarak hesaplanmıştır. Bunun yanında nem desorpsiyon hızı ve şarj verimi sırasıyla 6.5 g/dak ve %38 olarak elde edilmiştir. Çalışmanın son bölümünde, elde edilen deneysel veriler yardımıyla güneş enerjili TID sisteminin Kuzey Kıbrıs koşullarında mahal ısıtmada kullanımının ekonomik fizibilitesi geleneksel ısı pompası sistemleri ile karşılaştırmalı olarak analiz edilmiştir. Bu amaçla, DesignBuilder programında 90 m2 yüzey alanına sahip bir bina tasarlanarak yıllık ısı yükü hesaplanmıştır. Analiz sonuçlarına göre bina yıllık ısı yükü 1366 kWs olarak belirlenmiş, bu ısı yükünü karşılayabilmek için gerekli TID hacmi 8.75 m3 olarak hesaplanmştır. Yapılan fizibilite analizi güneş enerjili TID sistemiyle elde edilecek 10 yıllık ekonomik kazancın bügünkü değerinin $381 ve yatırım geri ödeme süresinin 6.4 yıl olduğunu göstermiştir. Bu bağlamda, yapılan analiz güneş enerjili TID sisteminin Kuzey Kıbrıs koşullarında uygulanmasının ekonomik olarak mümkün olduğunu göstermiştir. Anahtar kelimeler: Termokimyasal Isı Depolama, Güneş Enerjisi, Termodinamik Analiz, Gözenekli Taşıyıcı Matris, Kalsiyum Klorür, Kompozit Sorbent, Deneysel
Doctor of Philosophy in Mechanical Engineering. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2019. Supervisor: Assist. Prof. Dr. Devrim Aydın.
Keywords: Mechanical Engineering; Solar Energy--Heat Engineering; Thermochemical Heat Storage; Solar Energy; Thermodynamic Analysis; Porous Host Matrix; Calcium Chloride; Composite Sorbent; Experimental